Determinan Struktur Modal Perusahaan Property dan Real Estate Yang Terdaftar di BEI Periode 2017 - 2023 - Satrio Waliyudin Azhar; Adler Haymans Manurung; Jhonni Sinaga; Djuni Thamrin; AWN Fikri (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
Determinants of Capital Structure of Property and Real Estate Companies Listed on the IDX for the 2017-2023 Period. The success of a company can be seen from its capital structure. By evaluating achievements by analyzing Return On Assets, Company Size and Company Growth, it can be concluded whether these factors are able to influence the capital structure well or vice versa. This study aims to ROA, Size and Growth whether they have an influence on the capital structure (DER) listed on the Indonesia Stock Exchange (IDX) during the 2017-2023 period. This study uses secondary data as a data source, and a quantitative approach method. The population used in this study are companies listed on the Indonesia Stock Exchange for the 2017-2023 period. The results of this study indicate that ROA, Size and Growth have a positive and significant effect on Capital Structure, ROA has a positive and insignificant effect on Capital Structure, Size has a negative and significant effect on Capital Structure, and Growth has a positive and significant effect on Capital Structure